2013
DOI: 10.1177/1077546313493919
|View full text |Cite
|
Sign up to set email alerts
|

Chatter detection in milling machines by neural network classification and feature selection

Abstract: In modern industry, milling is an important tool when a high material removal rate is required. Chatter detection in this situation is a crucial step for improving surface quality and reducing both noise and rapid wear of the cutting tool. This paper proposes a new methodology for the chatter detection in computer numerical control milling machines. This methodology is based on vibratory signal analysis and artificial intelligence. The methodology consists of five major steps:(1) data acquisition, (2) signal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 31 publications
(34 reference statements)
0
47
0
2
Order By: Relevance
“…While performances of geostatistic interpolation, remote sensing retrieval, and air dispersion modeling are greatly influenced by the well-defined physical-chemical mechanisms of PM 2.5 pollution which have not been clearly disclosed so far, RBF neural network, due to the prominent self-learning ability and high simulation accuracy, has recently shown to be suitable for exploring the undefined relationships between PM 2.5 concentration and its influencing factors (Fang et al 2011;Lamraoui et al 2013;Zhao and Hasan 2013;Losser et al 2014). In studies that rely on RBF neural networks, variables were excessively limited to traffic emission, air pollutants' concentration, and meteorological factors such as temperature and pressure (Pérez et al 2000;Fang et al 2011;Zheng and Shang 2013;Losser et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While performances of geostatistic interpolation, remote sensing retrieval, and air dispersion modeling are greatly influenced by the well-defined physical-chemical mechanisms of PM 2.5 pollution which have not been clearly disclosed so far, RBF neural network, due to the prominent self-learning ability and high simulation accuracy, has recently shown to be suitable for exploring the undefined relationships between PM 2.5 concentration and its influencing factors (Fang et al 2011;Lamraoui et al 2013;Zhao and Hasan 2013;Losser et al 2014). In studies that rely on RBF neural networks, variables were excessively limited to traffic emission, air pollutants' concentration, and meteorological factors such as temperature and pressure (Pérez et al 2000;Fang et al 2011;Zheng and Shang 2013;Losser et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies combined SVM and signal processing technology to identify leaks, such as SVM and local mean decomposition method, fuzzy SVM, and wavelet packet denoising . Some researchers reported that ANN has better performance in dealing with the complex nonlinear problems in AE‐based leak detection . Pressure at inlet and outlet and AE signals inside the pipe were used to train the ANN‐based leak classifier.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Some researchers reported that ANN has better performance in dealing with the complex nonlinear problems in AE-based leak detection. 26 Pressure at inlet and outlet 27 and AE signals inside the pipe 28 were used to train the ANN-based leak classifier. Further, momentum term and self-adaptive learning rate were adopted to solve the local optimal convergence of back propagation (BP) neural network.…”
Section: Introductionmentioning
confidence: 99%
“…La detección del fenómeno de las vibraciones regenerativas es un aspecto muy importante a considerar en la obtención de una buena calidad superficial en la pieza, la reducción del ruido y la disminución de desgaste de la herramienta de corte (Lamraoui et al, 2015). Ko y Shaw (2009) afirman que las vibraciones regenerativas que afectan el sistema permiten determinar el efecto regenerativo en la estabilidad dinámica del sistema y diferenciarlo del efecto de las vibraciones forzadas producidas por la frecuencia de entrada de dientes.…”
Section: Introductionunclassified